2020
DOI: 10.1016/j.ab.2020.113863
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of protein stability by temperature and chemical denaturation

Abstract: The stability of a protein is a fundamental property that determines under which conditions, the protein is functional. Equilibrium unfolding with denaturants requires preparation of several samples and only provides the free energy of folding when performed at a single temperature. The typical sample requirement is around 0.5 -1 mg of protein. If the stability of many proteins or protein variants needs to be determined, substantial protein production may be needed. Here we have determined the stability of acy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 41 publications
(41 reference statements)
1
28
0
Order By: Relevance
“…CI2 is a highly stable protein with free energy for folding, ∆Gf = 31 kJ/mol (Hamborg et al, 2020;Itzhaki et al, 1995) and, as previously shown (Zutz et al, 2020), when wild-type CI2 is expressed in the bacterial sensor system (Figure 1a) only little GFP is produced ( Figure 1b). The dynamic range of the GFP signal towards discovering stabilized variants (i.e.…”
Section: Facs Sorting Libraries Of Random Ci2 Variantssupporting
confidence: 65%
See 2 more Smart Citations
“…CI2 is a highly stable protein with free energy for folding, ∆Gf = 31 kJ/mol (Hamborg et al, 2020;Itzhaki et al, 1995) and, as previously shown (Zutz et al, 2020), when wild-type CI2 is expressed in the bacterial sensor system (Figure 1a) only little GFP is produced ( Figure 1b). The dynamic range of the GFP signal towards discovering stabilized variants (i.e.…”
Section: Facs Sorting Libraries Of Random Ci2 Variantssupporting
confidence: 65%
“…To measure the in vitro stability for folding we used our recently described combined twodimensional thermal and chemical protein unfolding assay, where the unfolding of the protein is followed by the change in intrinsic Trp fluorescence as the temperature is increased at multiple concentrations of denaturant ( Figure 1d) (Hamborg et al, 2020). The stabilities of the 27 CI2 variants cover a broad range from -7.4 kJ/mol to -38.5 kJ/mol including five variants that are more stable than the wild-type protein (Table 1 and Figure 1e).…”
Section: Selecting Variants For Further Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These plots are automatically generated by the control software of the Prometheus Panta instrument. For the combined chemical and thermal unfolding experiments, the data set of each protein was globally fitted to the thermodynamic two-state model recently presented 47 . The global fits are shown in supplementary figure 7.…”
Section: Combined Differential Scanning Fluorimetry (Dsf) and Dynamic Light Scattering (Dls) Experimentsmentioning
confidence: 99%
“…Interestingly, we find that significant aggregation is only observed in the absence of urea, as well as for the 1-2 lowest urea concentrations. This information allowed us to perform a global fit to a model of the temperature-dependent IgLC thermodynamic stability 47 , where we excluded the samples where aggregation was observed. Details of the modelling, which was performed directly on the fluorescence intensity rather than the ratio, can be found in the methods section.…”
Section: While Dt Aggmentioning
confidence: 99%